North American energy system responses to natural gas price shocks. (February 2021) - Brown, Maxwell; Siddiqui, Sauleh; Avraam, Charalampos; Bistline, John; Decarolis, Joseph; Eshraghi, Hadi; Giarola, Sara; Hansen, Matthew; Johnston, Peter; Khanal, Saroj; Molar-Cruz, Anahi
Abstract: As of 2020, North American natural gas extraction and use in the electricity sector have both reached all-time highs. The combination of North America's increased reliance on natural gas with a potential disruption to the natural gas market has several energy security implications. Additionally, policymakers interested in economic resiliency will find this study's results useful for informing the implications of the energy sectors' long-term planning and investment decisions. This paper evaluates how both the electricity and natural gas sectors could respond to hypothetical gas price shocks under different system configurations. We impose unforeseen natural gas price shocks under reference and alternative configurations resulting from a renewable generation mandate or variations to renewable capacity costs. Results from several different models are presented for the electricity and natural gas sectors separately for Canada, Mexico, and the United States. Generally, the US becomes more (less) reliant on electricity imports from Canada given a high (low) gas price shock but increases (decreases) exports to Mexico. The renewable mandate is demonstrated to buffer electricity price increases under high price shocks but price reductions under the low price shocks are dampened given less flexibility to take advantage of the low-priced natural gas. The United States is demonstrated to reduce natural gas production and net exports with high natural gas price shocks given a reduction in demand. Highlights: Electricity and natural gas sectors are simulated to face natural gas price shocks. Comparison of how Canada, Mexico, and USA energy sectors respond to the shocks. System buildout at time of shock varies by policy and market conditions. Results presented for seven models of different structure and focus.